Study of stability problems due to undesired coupling of a RF power amplifier using a distributed active transformer. Issue 11 (November 2015) - Park, Jonghoon; Lee, Changhyun; Park, Changkun
Abstract: In this study, we investigate the stability problems induced by undesired coupling between input feed lines and an output transformer for a linear CMOS power amplifier using a distributed active transformer (DAT) as an output balun. We extracted the losses of the input and output transformer, the undesired coupling, and the gains of the driver and the power stages to calculate the closed-loop gain. To determine the possibility of oscillation according to the location of the driver stage related to the undesired coupling and the closed-loop gain, we investigated the stability factor and stability circle. We show that the location of the driver stage of the power amplifier can be used to manage the value of the closed-loop gain. From the analyzed results, the driver stage of the linear power amplifier should be located outside the DAT to mitigate the stability issues.